1990
DOI: 10.1139/v90-057
|View full text |Cite
|
Sign up to set email alerts
|

Flash photolysis production of the tetrahedral intermediate of the methanolysis of methyl benzoate. Direct measurement of the rate of breakdown of the conjugate base form

Abstract: . Can. J. Chem. 68, 375 (1990). Laser flash photolysis in aqueous basic solutions of the ortho acid derivatives 1-(phenyldimethoxymethyl)benzimidazole 2 and 4-bromo-1-(phenyldimethoxymethyl)imidazole 3 results in production of the phenyldimethoxymethyl cation, which has A, , at 260 nm. The cation decays in reactions with water (k = 9.9 X lo4 s-I) and hydroxide ion (2.5 X 10' M-' s-' )to finally yield methyl benzoate, whose formation was monitored at 234 nm. In solutions with pH 10-12, rate constants measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…As outlined in Figure 1 , the StEH1 reaction starts with nucleophilic attack on the bound epoxide to form an alkyl–enzyme intermediate, followed by general-base ester hydrolysis of the alkyl–enzyme intermediate that proceeds via a short-lived tetrahedral intermediate, which decomposes to the final product. As the last step is extremely fast and certainly not rate-limiting, 41 for computational simplicity we focused on the first two steps, which were described in terms of two valence bond structures, as illustrated in Figure 3 . Additionally, mutagenesis studies 4 provide evidence that D105 ( Figure 2 ) acts as the nucleophile to open the epoxide ring and that Y154 and Y235 are also crucial for the catalytic activity, forming an oxyanion hole to stabilize the alkyl–enzyme intermediate.…”
Section: Methodsmentioning
confidence: 99%
“…As outlined in Figure 1 , the StEH1 reaction starts with nucleophilic attack on the bound epoxide to form an alkyl–enzyme intermediate, followed by general-base ester hydrolysis of the alkyl–enzyme intermediate that proceeds via a short-lived tetrahedral intermediate, which decomposes to the final product. As the last step is extremely fast and certainly not rate-limiting, 41 for computational simplicity we focused on the first two steps, which were described in terms of two valence bond structures, as illustrated in Figure 3 . Additionally, mutagenesis studies 4 provide evidence that D105 ( Figure 2 ) acts as the nucleophile to open the epoxide ring and that Y154 and Y235 are also crucial for the catalytic activity, forming an oxyanion hole to stabilize the alkyl–enzyme intermediate.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of the base-catalyzed breakdown of cyclic hemiacetals with phenol (10) and carboxylate (1 1) leaving groups have shown that the class n mechanism is no longer followed. With hemiorthoester tetrahedral intermediates derived from benzoic acid, the basecatalyzed reaction was found to still follow a class n type of mechanism, but with the proton transfer step rate-limiting (12,13). This mechanism is enforced (2,14) by the short lifetime of the anionic intermediate in respect to its breakdown by expulsion of RO-, as in eq.…”
Section: [I B]])mentioning
confidence: 98%
“…We have described previously an approach for the oxocarbocation intermediates of acetal and ortho ester hydrolysis, where rate constants measured in strong acids were extrapolated to water with the assumption that differences between pairs of cations remain constant as the acidity is changed (24). This procedure was supported by observation of the required parallelism, albeit over a limited range in many cases, and through agreement with rate constants independently estimated by a "clock" approach (25 has been conclusively established through direct measurement in water using the technique of laser flash photolysis (26,27). Figure 3 shows data for phosphonium ions that allow for such an extrapolation.…”
Section: Lifetimes Of Phosphonium Ions In Watermentioning
confidence: 94%